Ring Party [part of Venice Design Week – 4th edition] - Roberta Bernabei (2013)
RING PARTY 66 anelli in mostra. The 2013 edition of Ring Party was be held in Treviso from 8th to 16th June in the historic thirteenth century Palazzo Ca' De Ricchi in via Barberia 25. RINGPARTY, as the name suggests is a yearly AGC event promoted by AGC directors and by members who work together to identify and propose the venue that will host the members' exhibition. The project was created with the intention of giving space to the object-jewel that mostly contains different meanings: a symbol of stability in a union, eternity, honour, as well as many legends and fairy tales, in which rings provide their protagonists with supernatural powers. The ring can be precious, but can also be interpreted in a very personal manner and made of different materials. Each ring presents the personality of the maker and bears a different meaning.